Timber Strength Grading as Necessary Basis for Structural Design in ex-YU Region: Part 2 - Tatjana Kočetov Mišulić; Aleksandra Radujković; Zdravko Popović; Ksenija Hiel (Drvna Industrija, 2024)
The aim of this paper is to contribute to the classification of structural timber in the ex-YU region into strength-class system through the application of experimentally obtained archive data in order to provide a realistic framework for most commonly used II grade (according to JUS) structural coniferous timber. The analysis of archive data was carried out on a sample of 150 specimens of structural size and based on the set of statistical requirements prescribed by EN standards, taking into account the change in disposition of loading in laboratory testing in the past and now. Statistical procedures prescribed by EN standards are given through calculation steps together with necessary adjustment factors that cover the size and number of specimens. The presented procedures given for structural-size specimens are also applicable to small clear specimens, so that a more comprehensive research and additional new examinations could be conducted with the available archive data simultaneously with the harmonization of the visual classification rules applied in the ex-YU region. The paper emphasises the direct dependence of the consistent application of the visual grading rules required by the relevant EN standard on strength-class system.